Effect of novel cycloaliphatic comonomer incorporation on the color stability of thermo-polymerized denture base resin - Ranganathan Ajay; Mohan Navinbharathy; Ranganathan Krishnaraj; Venkatraman Shanmugam Rajaganeshan; Muthupettai Varadharajan Srikanth; Karthigeyan Suma (Wolters Kluwer Medknow Publications, 2021)
Background: Denture during its in vivo service encounters myriad food pigments and numerous physico-mechanical dynamic changes. Denture discoloration is one of the unresolved problems that should be unraveled to satisfy the esthetic demands of the patients. Aim: This study aims to evaluate the color stability of a novel denture base copolymer with 10% and 20% (vol/vol) concentration of cycloaliphatic comonomer. Materials and Methods: Control group (G0) comprises specimens made without cycloaliphatic comonomer. The specimens of trial groups G10 and G20 were fabricated with 10% and 20% cycloaliphatic comonomer, respectively. For each group, thirty specimens (n = 30) were made. The specimens (n = 10) were immersed in three food colorant solutions (erythrosine, tartrazine, sunset yellow) for 56 days after artificial thermal aging. Ultraviolet-visible spectrophotometer was employed to measure the tristimulus values and calculate the color change (ΔE) of the specimens prior to and following rapid thermal aging or immersion of the specimens in the food colorants. Results: G0 showed the highest ΔE and G20 exhibited the least with each colorant. G10 had an intermediate imperceptible ΔE with each colorant. Also, significant differences (P = .000) existed between the food colorants within each group. The highest ΔE value was observed with sunset yellow and the lowest ΔE with tartrazine with each group. Conclusion: The addition of cycloaliphatic comonomer in denture base acrylic resins improved the color stability. The new copolymer with 20 Vol.% comonomer exhibited the highest color stability with all the food colorants.